Indicadores psíquicos de puérperas do alojamento conjunto do Hospital Universitário Júlio Muller de Cuiabá/MT e a interrupção precoce do aleitamento exclusivo - Almeida, Alessandra Messias de (2020)
Breast milk is recognized worldwide as the food with adequate and important nutritional properties for the baby. Its benefits are widely published by the organizations which are involved with this subject, however, breastfeeding rates in Brazil are below expectations. Considering that women suffer social pressures to breastfeed, which can result in emotional costs with an impact on their mental health, the objective of this study was to evaluate the maternal psychological condition during the exclusive breastfeeding process. This study was characterized as descriptive, field, longitudinal section and quantitative approach. The sample consisted of 30 mothers, aged 18 to 39 years (M = 26.96 and SD = 5.8), eight primiparous and 22 multiparous, from the joint accommodation of the Júlio Muller University Hospital (HUJM), in the city of Cuiabá -MT. The data collecting was divided into two stages, the first being within eight days after entry (AVG= 3.13 and SD= 1.99), individually, using the following methods: semi-structured interview, sociodemographic questionnaire, PHQ-9 questionnaire and the HTP graphic technique. The second stage was done from 100 to 190 days after delivery (AVG= 122.44 and SD= 21.37), through telephone contact/message contact via WhatsApp confirming adherence or early interruption of exclusive breastfeeding. Descriptive statistics techniques were used for the analysis of the results. Related to the socioeconomic status, the participants were young with high socioeconomic conditions. Moreover, most of them had incomplete high school and were experiencing a marital relationship. Regarding breastfeeding, 76.7% practiced exclusive breastfeeding in the first stage of data collecting and 50% in the second stage. The main reasons presented for interrupting exclusive breastfeeding were lack of milk production and milk insufficiency. As for the risk signs for the development of depression, high scores were found in half of the participants, of which 26,7% were moderately severe and 23,3% were at mild risk and indicated the main changes in their sleep, fatigue and appetite. Regarding the psychic conditions assessed by HTP technique, the small size is verified in all drawings presented as insecurity, diffidence and regression. It was observed the predominance of the left quadrant suggesting retraction, organicity, impulsivity, need for immediate gratification and regression. As for the details of each drawing which they had to identify themselves in relation to the House, plenty of them drew small doors with locks / hinges and windows with emphasis, suggesting defensive interpersonal contact and possible social ambivalence. The roofs were drawn with emphasis by the majority indicating the presence of fantasy and introversion. As for the details of the Tree, there was a predominance of the broad-based trunk suggesting a relationship of dependency, a cloud-shaped treetop suggesting the presence of fantasy and types of fruit trees indicating a relationship of dependency and immaturity. As for the details of the Person, it was verified that the majority drew a head with a large size indicating regressive condition and legs apart suggesting aggressiveness. Based on those study results we conclude that the psychic condition of the participants is in a regressed condition with emotional dependence and immaturity at that moment. Such results showed the importance of psychological assessment in the screening of depressive symptoms and maternal psychic conditions which can avoid damage to maternal mental health in the puerperium.